2021
DOI: 10.1016/j.ijrobp.2021.07.1011
|View full text |Cite
|
Sign up to set email alerts
|

Age, Race, and Digital Divide Index are Associated With Video Visit Completion for Patients Seen in Radiation Oncology

Abstract: The COVID-19 pandemic drove rapid adoption of telehealth across medicine, including radiation oncology, to minimize inperson contact. This exposed patient barriers to telehealth access and created care disparities in the absence of specific access assistance which have been little studied. A better understanding of these telehealth access barriers will help direct assistance resources to improve access in radiation oncology patients in the future. Materials/Methods: Data for all unique patient visits at a larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“… 9 , 10 , 11 , 15 In taking a more proactive approach to future infrastructure and development, Wosik et al 9 urged healthcare systems to create a more sustainable telehealth infrastructure that efficiently maximizes hospital staff and resources. In a systematic review of video visits completed for patients seen in radiation oncology during the peak of the pandemic, Cousins et al 17 found that certain patient characteristics (e.g., older age, minority background, geographical location) are less likely to be able to access care through video visits. Thus, the development of ways to identify underserved groups and methods to bridge the digital divide are warranted for successful telehealth outcomes.…”
Section: Introductionmentioning
confidence: 99%
“… 9 , 10 , 11 , 15 In taking a more proactive approach to future infrastructure and development, Wosik et al 9 urged healthcare systems to create a more sustainable telehealth infrastructure that efficiently maximizes hospital staff and resources. In a systematic review of video visits completed for patients seen in radiation oncology during the peak of the pandemic, Cousins et al 17 found that certain patient characteristics (e.g., older age, minority background, geographical location) are less likely to be able to access care through video visits. Thus, the development of ways to identify underserved groups and methods to bridge the digital divide are warranted for successful telehealth outcomes.…”
Section: Introductionmentioning
confidence: 99%